A new species of gecko of the genus Lygodactylus (Sauria: Gekkonidae) from southeastern Kenya - Malonza, Patrick K.; Bauer, Aaron M.; Granthon, Carolina; Williams, Dean A.; Wojnowski, David (Zootaxa, 2019)
A new species of gecko, Lygodactylus tsavoensis sp. nov., is described from Tsavo Conservation Area in southeastern Kenya. It is a member of the Lygodactylus picturatus group and is distinguished from other closely related species by its small size (maximum 35 mm SVL), five postpostmental scales, seven precloacal pores, and a distinctive color pattern. A pale Y-shaped mark on the crown continues along the vertebral midline to the tail base and is flanked by a pair of dark stripes. In addition to its morphological differences, the new species is genetically divergent from its most closely related congeners, L. keniensis and L. wojnowskii. The new species is widespread in the southern and southeastern arid lands within the Tsavo Conservation Area, mainly in Taita-Taveta, Kitui, Makueni, Kajiado, Kilifi, Kwale and Tana River Counties. It is chiefly associated with bushland with short trees, including areas of anthropogenic influence.